2011
DOI: 10.4049/jimmunol.1003642
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Murine High-Affinity IgG Receptor FcγRIV Is Sufficient for Autoantibody-Induced Arthritis

Abstract: K/BxN serum-induced passive arthritis was reported to depend on the activation of mast cells, triggered by the activating IgG receptor FcγRIIIA, when engaged by IgG1 autoantibodies present in K/BxN serum. This view is challenged by the fact that FcγRIIIA-deficient mice still develop K/BxN arthritis and because FcγRIIIA is the only activating IgG receptor expressed by mast cells. We investigated the contribution of IgG receptors, IgG subclasses, and cells in K/BxN arthritis. We found that the activating IgG2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 30 publications
9
107
0
Order By: Relevance
“…Using "Fc␥RIV-only" mice we reported that Fc␥RIV induced arthritic inflammation in the passive K/BxN model of arthritis 66 in the presence of IgG2-immune complexes. 41 These results are in agreement with those obtained when inducing collagen-induced arthritis in 3KO mice. 65 "Fc␥RIV-only" mice also developed lung inflammation after activation of alveolar macrophages in the presence of IgE-immune complexes, 26 and experimental thrombocytopenia induced by antiplatelet mouse IgG2a mAbs.…”
Section: Data Using Fc␥r-deficient Micesupporting
confidence: 82%
See 2 more Smart Citations
“…Using "Fc␥RIV-only" mice we reported that Fc␥RIV induced arthritic inflammation in the passive K/BxN model of arthritis 66 in the presence of IgG2-immune complexes. 41 These results are in agreement with those obtained when inducing collagen-induced arthritis in 3KO mice. 65 "Fc␥RIV-only" mice also developed lung inflammation after activation of alveolar macrophages in the presence of IgE-immune complexes, 26 and experimental thrombocytopenia induced by antiplatelet mouse IgG2a mAbs.…”
Section: Data Using Fc␥r-deficient Micesupporting
confidence: 82%
“…38 Notably, human FcRn has no affinity for mouse IgG1, but its low affinity for mouse IgG2a and IgG2b 39 is sufficient to restore a mouse IgG2-dependent autoimmune arthritis in a transgenic mouse model (mice deficient for FcRn and transgenic for hFcRn). 40,41 Major differences between human Fc␥R expression patterns and that of their mouse homolog also exist: (1) the expression of mouse, but not human, Fc␥RI is restricted to monocyte-derived DCs; (2) the expression of human, but not mouse, Fc␥RIIB is mainly restricted to B cells and basophils; (3) the expression of human Fc␥RIIIA, but not mouse Fc␥RIII, is restricted to NK cells and monocytes/ macrophages; (4) Fc␥RIV exist in mice but not in humans 24,25 ; and (5) Fc␥RIIA, Fc␥RIIC, and Fc␥RIIIB exist in humans but not in mice. 12 Fc␥R homologs between humans and mice may thus be defined based on expression and ligand binding, rather than on amino acid similarity.…”
Section: Human Versus Mouse Fc␥rsmentioning
confidence: 99%
See 1 more Smart Citation
“…A nonlethal PSA could also be observed in Rag2 -/-5KO mice injected with IC made of GPI and K/BxN serum (GPI/anti-GPIinduced PSA) ( Figure 3E), which contains polyclonal IgG1 and IgG2 anti-GPI antibodies (25,26). Neutrophil depletion abolished this GPI/anti-GPI-induced PSA in Rag2 -/-5KO mice ( Figure 3F).…”
Section: Resultsmentioning
confidence: 84%
“…Various FcgRIV-dependent disease models were abolished using the same dose of the same batch of anti-FcgRIV mAbs (data not shown and Refs. 8,14), indicating that FcgRIV was efficiently and systemically blocked in vivo. Notably, this mAb does not, by itself, induce FcgRIV-mediated cell activation in vitro (9).…”
Section: B16-luc2mentioning
confidence: 99%